BEDAQUILINE SEBAGAI TATALAKSANA MULTIDRUG-RESISTANT TUBERCULOSIS (MDR-TB): SEBUAH KAJIAN SISTEMATIS DAN META ANALISIS - Buana, Belva Bhadranitya (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2024)
ABSTRAK Background: MDR TB is TB that is resistant to at least 2 types of first-line anti-tuberculosis drugs, namely isoniazid and rifampicin. Treatment requires a longer duration and is accompanied by worse side effects, high costs, and logistical constraints. Bedaquiline (BDQ) is a diarylquinoline compound which exhibits earlier culture conversion and minimal side effects, compared to other MDR TB drugs, making it possible to eliminate adherence problems in MDR TB patients. This meta-analysis aims to assess the effect of BDQ administration on MDR TB patients and other related aspects. Methods: Systematic studies were carried out following the PRISMA rules using online databases, namely PubMed, ScienceDirect, and Cochrane. Studies assessing the effect of BDQ in MDR TB patients and compliance with inclusion criteria were included in this systematic review. The risk of bias of each inclusion study was assessed using the CONSORT, TREND and STROBE criteria. Meta-analysis with the fixed-effects method was then performed to obtain the combined Mean Difference (MD) of all inclusion studies along with the 95% Confidence Interval (CI). Discussion: 17 studies involving 2454 patients were included in this systematic review. It was found that administration of BDQ in MDR TB patients increased the likelihood of conversion culture becoming negative with an RR of 1.39 (95% CI = 1.26-1.53 ; I2 = 29% ; p <0.00001), and decreased the likelihood of relapse with RR of 0.40 (95% CI = 0.21-0.75 ; I2 = 0% ; p = 0.004) significantly compared to the control group. As well as being able to reduce the death rate from MDR TB. Conclusions: BDQ administration showed a positive effect on the possibility of earlier culture conversion, the possibility of relapse, and the mortality rate